Relationship between Physical Fitness, Athlete Leadership Related to Athletic Performance, Athletic Psychology and Sport Athletic Satisfaction in China - Du Chenglin, (Revista de Psicología del Deporte (Journal of Sport Psychology), 2021)
The current study aims to analyze the relations between physical fitness, athlete leadership, athletic performance, athletic psychology and athletic satisfaction of sports center in China. This study also examines the mediating role of athletic performance and athletic psychology among the nexus of physical fitness, athlete leadership, and athletic satisfaction of sports centers in China. This study has used the questionnaires adopted from past studies to collect the data from the respondents. This study also used the smart-PLS to test the reliability and validity and also to test the hypotheses of the study. The results have exposed that physical fitness and athlete leadership have significant positive relations with athletic performance and athletic psychology while athletic performance and athletic psychology also have significant positive relations with athletic satisfaction of sports center in China. The results also indicated that athletic performance significantly mediates among the relation of physical fitness, athlete leadership, and athletic satisfaction while athletic psychology significantly mediates among the relation of athlete leadership and athletic satisfaction.